RITUAL PERANG DALAM KEBUDAYAAN SUKU DAYAK - Hanifi, Muhammad Luthfan (Sabda: Jurnal Kajian Kebudayaan, 2016)
This paper is concerned with the rituals of Dayak tribe that are performed before, during, and after a war. Dayak tribe is one of many tribes in Indonesia that is very conservative towards their cultural tradition. The rituals were conserved until Tumbang Anoi treaty in 1894. The rituals are rarely performed as Dayak tribe tries to avoid war with other Dayak tribes since Dayak has 405 clans or other tribes. Before Tumbang Anoi treaty, Dayak tribe was active in performing the rituals as there were wars among their clans or against colonialist. After Tumbang Anoi treaty, Dayak is rarely involved in war except they feel that their pride or tradition is humiliated. Nowadays, the rituals which consist of ceremonies, dances, and headhunting or Kayau are only performed as guests reception except the headhunting part